Pengaruh Self-Confidence Terhadap Hasil Belajar Siswa - Ika Septi Hidayati; Evitri Setiyaningsih; Poppy Aina Rahma Sagita (CV. Kurnia Grup, 2026)
This study aims to analyze the effect of self-confidence on student learning outcomes at MTs Darul Ulum Muhammadiyah Galur. The method used is an experiment with a Quasi-Experimental Design. The research population includes all ninth-grade students, with a sampling technique that designates ninth-grade class B as the experimental class and ninth-grade class C as the control class. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis tests using IBM SPSS Statistics 25 software. Based on the results of the hypothesis test using the Paired Sample T-Test, a t-value of 6.068 was obtained, which was greater than the t-table value of 1.686 (6.068 > 1.686). Thus, H0 was rejected and H1 was accepted, indicating that there was a significant effect of self-confidence on student learning outcomes.